Engineering Molecular Polymerization for Template‐Free SiOx/C Hollow Spheres as Ultrastable Anodes in Lithium‐Ion Batteries. (27th March 2021) - Zhou, Xiaoming; Liu, Yang; Ren, Yang; Mu, Tiansheng; Yin, Xucai; Du, Chunyu; Huo, Hua; Cheng, Xinqun; Zuo, Pengjian; Yin, Geping
Abstract: SiO x /C composites with a void‐reserving structure are promising anodes for lithium‐ion batteries. However, the facile and controllable synthesis of uniformly dispersed SiO x and carbon components, simultaneously incorporating ample voids, still remains a great challenge. Herein, a molecular polymerization strategy is devised to construct SiO x /C hollow particles for lithium‐ion batteries. 3‐aminopropyltriethoxysilane and dialdehyde molecules are judiciously engineered as silicon and carbon precursors to produce the polymer hollow spheres (PHSs) through a one‐step aldimine condensation without any template and additive. A range of PHSs is obtained using terephthalaldehyde, glutaraldehyde, and glyoxal as the crosslinkers, demonstrating the high tunability of the strategy. Importantly, in situ pyrolysis of the PHSs warrants the homogeneous incorporation of SiO x (< 5 nm) in carbon hollow capsids at a nanocluster scale. The obtained SiO x /C hollow spheres exhibit excellent Li + ‐ion storage behaviors, including cycling lifespan, coulombic efficiency, and rate performance. The superior performance is attributed to the well‐dispersed SiO x nanoclusters in carbon substrate and the hollow structure. This molecular polymerization approach not only enables Si‐based hollow composites effective and scalable anode materials but also opens up a new avenue for the controllable synthesis of template‐free hollow architectures. Abstract : A range of template‐free SiO x /C hollow particles equipped with the uniform dispersion of two components at a nanocluster scale are prepared via the aldimine condensation strategy. The resultant SiO x /C hollow anodes display excellent Li + ‐ion storage behaviors, which indicate that the developed molecular polymerization methodology is an effective and scalable approach for practical Si‐based hollow anodes.